The excellent mind : intellectual virtues for everyday life - King, Nathan L. (Oxford : Oxford University Press, 2021)
"What makes for a good education? What does one need to count as well-educated? Knowledge, to be sure. But knowledge is easily forgotten, and today's knowledge may be obsolete tomorrow. Skills, particularly in critical thinking, are crucial as well. But absent the right motivation, graduates may fail to put their skills to good use. In this book, Nathan King argues that intellectual virtues-traits like curiosity, intellectual humility, honesty, intellectual courage, and open-mindedness-are central to any education worthy of the name. Further, such virtues are crucial to our functioning well in everyday life, in areas as diverse as personal relationships, responsible citizenship, civil discourse, and personal success. Our struggles in these areas often result from a failure to think virtuously. Drawing upon recent work in philosophy and psychology, King paints a portrait of virtuous intellectual character-and of the vices such a character opposes. Filled with examples and applications, this book introduces readers to the intellectual virtues: what they are, why they matter, and how we can grow in them"--
Includes bibliographical references and index.
Keywords: Virtue epistemology